Evaluating the Usability of a Free Electronic Health Record for Training. - Hoyt, Robert; Adler, Kenneth; Ziesemer, Brandy; Palombo, Georgina (Perspectives in Health Information Management)
The United States will need to train a large workforce of skilled health information technology (HIT) professionals in order to meet the US government's goal of universal electronic health records (EHRs) for all patients and widespread health information exchange. The Health Information Technology for Economic and Clinical Health (HITECH) Act established several HIT workforce educational programs to accomplish this goal. Recent studies have shown that EHR usability is a significant concern of physicians and is a potential obstacle to EHR adoption. It is important to have a highly usable EHR to train both clinicians and students. In this article, we report a qualitative-quantitative usability analysis of a web-based EHR for training health informatics and health information management students.